2009
DOI: 10.1038/nchembio.255
|View full text |Cite
|
Sign up to set email alerts
|

Natural amino acids do not require their native tRNAs for efficient selection by the ribosome

Abstract: The involvement of tRNA structural elements beyond the anticodon in aminoacyl-tRNA (aa-tRNA) selection by the ribosome has revealed that substrate recognition is considerably more complex than originally envisioned in the adaptor hypothesis. By combining recent breakthroughs in aa-tRNA synthesis and mechanistic and structural studies of protein synthesis, we ask if aa-tRNA recognition further extends to the amino acid, thereby explaining various translation disorders exhibited by misacylated tRNAs. Contrary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 50 publications
3
47
0
3
Order By: Relevance
“…It was believed that the naturally misacylated tRNA intermediates would not be used for protein synthesis since EF-Tu was shown to discriminate against Glu-tRNA Gln and Asp-tRNA Asn (Roy et al , 2007). However, expression of non-discriminatory AspRSs in trans results in significant Asn-to-Asp mistranslation in E. coli (Ruan et al , 2008, Nair et al , 2016), which is consistent with results showing that the ribosome can use certain misacylated tRNAs almost indistinguishably from correctly acylated tRNAs (Effraim et al , 2009). It has recently been shown that Mycobacterium tuberculosis , which makes charged tRNA Gln and tRNA Asn through the tRNA dependent transamidation pathway, naturally uses the misacylated Glu-tRNA Gln and Asp-tRNA Asn in translation (Su et al , 2016).…”
Section: Inherent Mistranslationsupporting
confidence: 88%
“…It was believed that the naturally misacylated tRNA intermediates would not be used for protein synthesis since EF-Tu was shown to discriminate against Glu-tRNA Gln and Asp-tRNA Asn (Roy et al , 2007). However, expression of non-discriminatory AspRSs in trans results in significant Asn-to-Asp mistranslation in E. coli (Ruan et al , 2008, Nair et al , 2016), which is consistent with results showing that the ribosome can use certain misacylated tRNAs almost indistinguishably from correctly acylated tRNAs (Effraim et al , 2009). It has recently been shown that Mycobacterium tuberculosis , which makes charged tRNA Gln and tRNA Asn through the tRNA dependent transamidation pathway, naturally uses the misacylated Glu-tRNA Gln and Asp-tRNA Asn in translation (Su et al , 2016).…”
Section: Inherent Mistranslationsupporting
confidence: 88%
“…smFRET measurements have shown that the incoming aa-tRNA may reversibly sample EA-like and A/T-like ensembles before peptide bond formation occurs28, consistent with elbow accommodation preceding 3′-CCA accommodation. Other experiments have found that mischarging aa-tRNA (attaching the wrong amino acid) does not alter elbow dynamics37, which suggests elbow and 3′-CCA accommodation are separable events. Finally, a cryo-EM reconstruction of the ribosome in complex with the antibiotic HygA found the elbow to be in an accommodated position, while the 3′-CCA end was displaced from the A-site38.…”
mentioning
confidence: 91%
“…Computational3536 and experimental283738 studies have implicated the following sequence of conformational rearrangements during aa-tRNA accommodation: (1) aa-tRNA moves from an A/T to an elbow-accommodated (EA) conformation, (2) the aa-tRNA arm accommodates into the A-site and (3) the 3′-CCA end enters the peptidyl transferase centre (PTC). The first simulations of factor-free accommodation employed targeting techniques and showed that sequential movement of the elbow, arm and 3′-CCA end is sterically accessible35.…”
mentioning
confidence: 99%
“…Die Effizienz beider Verfahren sollte in einem einheitlichen Experiment gezeigt werden, wie es im Haupttext beschrieben ist. Auf die graphische Darstellung der Machbarkeitsstudie für den ortsspezifischen In-vivo-Einbau zweier nichtkanonischer Aminosäuren durch Schultz und Mitarbeiter [31] [51] zeigt, dass die Translationsmaschinerie nicht zwischen richtig beladenen und fehlacylierten tRNAs unterscheidet. Es konnten jedoch kleine, aber reproduzierbare Unterschiede in der Dynamik der Ribosomzyklen mit fehlbeladenen tRNAs beobachtet werden.…”
Section: Abbildung 2 Zwei Methoden Zum Parallelen Einbau Zweier Nichunclassified